A lab of my own - Schwartz, Neena B. (Value Inquiry Book Series, 2010)
What was it like to be a woman scientist battling the "old boy's" network during the 1960s and 1970s? Neena Schwartz, a prominent neuroendocrinologist at Northwestern University, tells all. She became a successful scientist and administrator at a time when few women entered science and fewer succeeded in establishing independent laboratories. She describes her personal career struggles, and those of others in academia, as well as the events which lead to the formation of the Association of Women in Science, and Women in Endocrinology, two national organizations, which have been successful in increasing the numbers of women scientists and their influence in their fields. The book intersperses this socio-political story with an account of Schwartz's personal life as a lesbian and a description of her research on the role of hormones in regulating reproductive cycles. In a chapter titled "Don't Ask, Don't Tell," she examines the "evidence" from a scientist's point of view for the hormonal and genetic theories for homosexuality. Other chapters provide advice on mentoring young scientists and a discourse on why it matters to all of us to have more women doing and teaching science. She also describes the process of putting together an interdisciplinary Center on Reproductive Science at Northwestern, which brought together basic and clinical scientists in an internationally recognized program of research and practice.